Mother's Education and Toddler Age Affect Mother of Toddler's Activity to Posyandu Jiken Village, Jiken District, Blora Regency - Fitrianika Maya Dewi; Umaroh Umaroh; Triana Sri Hardjanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
In the Jiken Health Center area, Jiken Village is the village with the lowest Posyandu visit coverage in 2019 (41.4%). The purpose of this study was to analyze the factors that influence the activity of mothers under five to the Posyandu in Jiken Village. This research is a quantitative research with a cross sectional research design. The study population was mothers with children aged 12-59 months (387 mothers). Sampling using simple random sampling as many as 88 mothers. Data retrieval using Google Forms and interviews via telephone. To verify data on visits to children under five and immunizations, the researchers looked at the Posyandu register book and the village midwife cohort. With the Chi square test, the results showed that there was a relationship between the mother's level of education (ρ value 0.001), toddler age (ρ value 0.000) and the activeness of the mother under five at the Posyandu. There was no relationship between the level of knowledge (value 0.678), occupation (value 0.183) , immunization status (p value 0.162) with the activeness of mothers under five to the posyandu. From the results of the study, it was found that the activity of mothers under five to the posyandu was 47.7%, so mothers should always bring their toddlers to the posyandu. Posyandu should be integrated with PAUD and TK. It is hoped that this research can be a reference for further research materials.Keywords : Toddler Posyandu; education; knowledge; occupation; immunization status